BTK Promotes Atherosclerosis by Regulating Oxidative Stress, Mitochondrial Injury, and ER Stress of Macrophages. (27th May 2021) - Qiu, Junxiong; Fu, Yuan; Chen, Zhiteng; Zhang, Lisui; Li, Ling; Liang, Diefei; Wei, Feng; Wen, Zhuzhi; Wang, Yajing; Liang, Shi
Abstract : Atherosclerosis (AS) is a chronic metabolic disease in arterial walls, characterized by lipid deposition and persistent aseptic inflammation. AS is regarded as the basis of a variety of cardiovascular and cerebrovascular diseases. It is widely acknowledged that macrophages would become foam cells after internalizing lipoprotein particles, which is an initial factor in atherogenesis. Here, we showed the influences of Bruton's tyrosine kinase (BTK) in macrophage-mediated AS and how BTK regulates the inflammatory responses of macrophages in AS. Our bioinformatic results suggested that BTK was a potential hub gene, which is closely related to oxidative stress, ER stress, and inflammation in macrophage-induced AS. Moreover, we found that BTK knockdown could restrain ox-LDL-induced NK- κ B signaling activation in macrophages and repressed M1 polarization. The mechanistic studies revealed that oxidative stress, mitochondrial injury, and ER stress in macrophages were also suppressed by BTK knockdown. Furthermore, we found that sh-BTK adenovirus injection could alleviate the severity of AS in ApoE -/- mice induced by a high-fat diet in vivo. Our study suggested that BTK promoted ox-LDL-induced ER stress, oxidative stress, and inflammatory responses in macrophages, and it may be a potential therapeutic target in AS.